Experimental constraints on the role of dynamic recrystallization on resetting the Ti‐in‐quartz thermobarometer. Issue 12 (14th December 2015) - Nachlas, W. O.; Hirth, G.
Abstract: We conducted deformation experiments on Ti‐doped quartz aggregates to investigate the effect of crystal‐plastic deformation and dynamic recrystallization on Ti substitution in quartz. Shear experiments were conducted at 1.0 GPa and 900°C at a constant shear strain rate (~5 × 10 −6  s −1 ) for progressively longer intervals of time (24, 48, and 72 h). Equivalent experiments were conducted under hydrostatic stress to compare the effect of deformation relative to static crystallization. A novel quartz‐doping technique is used to synthesize a quartz aggregate consisting of two layers with Ti concentrations above and below the predicted solubility level for the experimental conditions. Samples deformed to progressively higher shear strain by dislocation creep accommodated by a combination of subgrain rotation and grain boundary migration recrystallization show a strengthening of the crystallographic preferred orientation that correlates with a progressive evolution of Ti concentrations. Quartz grains in the highest strain, most strongly recrystallized samples have Ti concentrations that are most similar to undeformed quartz grown in hydrostatic annealing experiments. Cathodoluminescence (CL) analysis of intragrain variations in Ti content reveals core and rim zoning present in the starting material that becomes progressively homogenized with increasing strain—recrystallized quartz in the highest‐strain samples exhibits a uniform CL signal. We conclude that dynamic recrystallization enhances the kinetics of trace element equilibration in quartz, illustrating that Ti‐in‐quartz thermobarometry is capable of recording the conditions of ductile shearing. Key Points: Dynamic recrystallization reequilibrates Ti concentrations in quartz Titania buffering can be upheld by aqueous solution Ti‐in‐quartz thermobarometry can retrieve the P‐T conditions of ductility